Mätning av egenskaper hos elmotor och transformatorplåt - Bajra, Mernis (My University, 2013)
Core loss measurements have been done. Because of the low magnetization current of the toroid the current was measured with a current transducer of model LA 100-S/SP1 and the voltage was measured with a voltage probe of model TT-SI9101 for better accuracy. The knowledge of the current and voltage made it possible to calculate the magnetic field strength and the magnetic field density and further with that the core losses. The obtained losses did not match with the losses given by the datasheet. The reason for the mismatch can be that the dimensions of the toroid core contribute in measuring the B-field value wrong.
Keywords: Elkraftteknik; Electric power engineering